Risk factors for perioperative nerve injury associated with total knee arthroplasty: Analysis of a national administrative database - Rahul H. Jayaram; Lucas Kim; Wesley Day; Rushabh H. Doshi; Lee E. Rubin; Jonathan N. Grauer (PLoS ONE, 2025)
Introduction Nerve injury related to total knee arthroplasty (TKA) is a rare but serious complication. Previous studies identifying risk factors for nerve injury related to TKA have been constrained by institutional data or small cohorts. The current study utilized a comprehensive, national, administrative database to investigate independent risk factors for nerve injury associated with TKA. Materials and Methods The PearlDiver M161 database was queried for adult TKA procedures performed between 2010 and 2022. Cases with postoperative nerve injury within 90 days of surgery were identified. Factors such as patient age, sex, body mass index (BMI), Elixhauser Comorbidity Index (ECI), fracture indication, and type of surgery (primary vs. revision) were evaluated for their correlation with nerve injury using multivariate analyses. Results Out of 1,517,637 TKA procedures, nerve injury was identified for 4,480 (0.3%). Multivariate analysis identified the following independent risk factors for nerve injury, listed in decreasing order of odds ratio (OR): revision surgery (OR: 1.68), female sex (OR: 1.31), ECI ≥ 5 (OR: 1.27), and younger age (OR: 1.02 per decreasing decade) (P < 0.05 for each). Factors not significantly associated with nerve injury included underweight BMI (<20 kg/m2) and fracture indication. A decreased risk of nerve injury was observed in individuals with a BMI ≥ 35 kg/m2 (OR: 0.80, P = 0.002). Discussion As expected, the incidence of nerve injury following TKA was low at 0.3%. Independent risk factors were identified for this adverse outcome, with the highest risk associated with revision surgeries. These findings, drawn from the largest cohort studied to date, offer valuable insights for risk stratification, and should inform patient discussions.